The Formation of Prosociality: Causal Evidence on the Role of Social Environment - Kosse, Fabian; Deckers, Thomas; Pinger, Pia; Schildberg-Hörisch, Hannah; Falk, Armin (Journal of Political Economy, 2020)
This study presents evidence on the role of social environment for the formation of prosociality. We show that socioeconomic status (SES) as well as intensity of mother-child interaction and mothers? prosocial attitudes are related to elementary school children?s prosociality. We also present evidence on a randomly assigned variation of the social environment, providing children with a mentor for 1 year. Our data reveal a significant and persistent increase in prosociality in the treatment relative to the control group. Moreover, enriching the social environment closes the prosociality gap between low- and high-SES children. A mediation analysis suggests that prosociality develops in response to prosocial role models and intense social interactions.